The Pupae of Culicomorpha—Morphology and a New Phylogenetic Tree - Borkent, Art (Zootaxa, 2012)
The pupae of each of the families of the Culicomorpha are described and, for the first time, their structures homologized.A glossary provides a standard set of terms to be applied to each structure, including a common chaetotaxy. A cladisticanalysis incorporates information from each life stage, including a number of new features discovered from the pupalstage, to provide a new phylogenetic hypothesis, as well as indicating autapomorphies for each family. Analysisincluded states for one egg, 21 larval, 33 pupal, and 37 adult characters. The Chironomidae is the sister group of allremaining Culicomorpha, the Ceratopogonidae is the sister group of Thaumaleidae + Simuliidae and these three arenewly recognized as members of the re-defined superfamily Simulioidea. The superfamily Culicoidea are the sistergroup of the Simulioidea and include, as previous work has already demonstrated, the Dixidae as the sister group ofCorethrellidae + Chaoboridae + Culicidae. Corethrellidae is the sister group of Chaoboridae + Culicidae. Thesuperfamily Chironomoidea now includes only Chironomidae.Analysis of the fossil record shows that the Chironomidae (and the Culicomorpha) originated in the Triassic andboth Simulioidea and Culicoidea were present by 176 million years ago in the Jurassic. Phylogenetic patterns are used tointerpret bionomic features such as differences in the nature of blood-feeding by adult females, daytime or nighttimefeeding by adult females, and occurrence of immature stages in aquatic habitats. Chironomidae do not feed on blood asadults and have likely diversified by invading virtually all aquatic habitats as larvae. Its sister group is more than twiceas diverse and feeding on vertebrate blood is strongly correlated with high diversification within the Simulioidea +Culicoidea (likely because a reliable source of protein was available to dispersing females since the Triassic fromterrestrial vertebrates). Families with blood-feeding females have larger numbers of species than do those without thisbehaviour. Each family in the Simulioidea + Culicoidea have specialized larval habitats or specialized habits, largely inaquatic habitats where Chironomidae are either not, or are marginally present, suggesting a level of competitive exclusion by the Chironomidae.